The Vargas government and the reordering of professional technical education: the implementation of the Industrial Liceu in Ceará (Research, Society and Development, 2019)
With the Revolution of the 1930s, when Getúlio Vargas became president, a series of profound changes began in the organization of Brazilian society. A new phase in the country's history, which brought significant changes to the educational project in Brazil, was then inaugurated. This article intends to discuss some educational reforms approved during the years of 1930 to 1945, when the country was governed by Getúlio Vargas, prioritizing the reorganization of professional technical education. For the development of the present study, the qualitative approach was chosen, using bibliographic research as a research method. For this, the reforms that reordered the Brazilian educational system during this period are initially presented, seeking to reflect on the legislation that has directly impacted the professional technical education. Finally, it is concluded that the reordering of professional technical education has proved, in practice, a way of promoting the workers formation according to the labor market needs, where the dualism of Brazilian education has been maintained.